UNIT 9.24 Analysis and Annotation of Whole‐Genome or Whole‐Exome Sequencing–Derived Variants for Clinical Diagnosis. (18th October 2013) - Worthey, Elizabeth A.
Abstract: Over the last several years, next‐generation sequencing (NGS) has transformed genomic research through substantial advances in technology and reduction in the cost of sequencing, and also in the systems required for analysis of these large volumes of data. This technology is now being used as a standard molecular diagnostic test under particular circumstances in some clinical settings. The advances in sequencing have come so rapidly that the major bottleneck in identification of causal variants is no longer the sequencing but rather the analysis and interpretation. Interpretation of genetic findings in a clinical setting is scarcely a new challenge, but the task is increasingly complex in clinical genome‐wide sequencing given the dramatic increase in dataset size and complexity. This increase requires the development of novel or repositioned analysis tools, methodologies, and processes. This unit provides an overview of these items. Specific challenges related to implementation in a clinical setting are discussed. Curr. Protoc. Hum. Genet . 79:9.24.1‐9.24.24. © 2013 by John Wiley & Sons, Inc.